Reframing Islamic Education Under Globalization: A Systematic Review Of Human Rights Integration Through The Maqāṣid Al-Sharīʿah Framework - Muhammad Arwani; Irpan Hilmi; Muhamad Farid Rifai Iskandar; Ahmad Syahid; Mohamad Erihadiana; Uus Ruswandi (International Journal of Interdisciplinary Research, 2026)
Globalization has significantly reshaped contemporary education through digitalization, transnational knowledge circulation, and global normative frameworks, compelling Islamic education to adapt while preserving its moral and spiritual foundations. Although existing studies discuss globalization, Islamic education reform, and human rights separately, there remains a lack of systematic synthesis integrating these dimensions. This study addresses this gap by conducting a PRISMA-based Systematic Literature Review of peer-reviewed journal articles (2015–2025) indexed in Scopus, Web of Science, and Google Scholar. Using thematic synthesis guided by the maqāṣid al-sharīʿah framework, the review analyzes how globalization drives paradigm shifts in Islamic education and shapes and mediates the integration of human rights principles. The findings reveal a transition toward learner-centered pedagogy, competency-based curricula, and adaptive institutional governance aligned with ḥifẓ al-ʿaql, while human rights integration remains uneven and often normative. Maqāṣid-based reasoning emerges as a key mediating framework that contextualizes human rights within Islamic educational values. The study highlights the need for maqāṣid-oriented policies and governance reforms to ensure that globalization and human rights advance intellectual development, dignity, justice, and moral responsibility in Islamic education.